Porcellio sp. على افراد الجنس Datura stramonium L. دراسة تاثير مسحوق أوراق نبات الداتورة - ناديا عماد الامين; سناريا عباس العلاق (University of Thi-Qar Journal of Science, 2019)
This study aimed to know the effect of the leaves powder of Datura stramonium L. in the genus Porcellio sp, by feeding on leaves powder. The P.sp. were classifided into tow groups,( immature and mature) stages , and notice the effects of (stage-soil-time) on mortality. The results revealed that there was a mortality in the P.sp. , the mortality rate of immature stage was (7.77) , (10.00 ) and for the mature stage (4.44) ,(6.00) when the natural soil were existed and not , for each stage respectively, the existence of soil reduced the poison effected of the plant leaves for each stage .In addition the mortality of immature stage spended a few times, after one day than the other in the tenth day of experiment.